C1, 2 Pedicle Screw Fixation in Treating Atlantoaxial Instability Guided by Surgical CT Navigation. (May 2014) - Jiang, T.; Ren, X.; Wang, J.; Chu, T.; Zhang, Z.; Wang, W.
Introduction: To evaluate the accurate rate of insertion and the short-term curative effect of C1, 2 pedicle screw internal fixation for atlanto-axial instability guided by surgical CT navigation. Materials and Methods: Seven patients with atlanto-axial instability were treated by C1, 2 pedicle screw internal fixation and bone graft fusion, guided by surgical CT navigation, including three cases of congenital dysplasia of odontoid process, three cases of atlantoaxial instability, and one case of old odontoid process fracture. Results: There was no vascular or neural injury found. The patients were followed up for 3 to 15 months. The clinical symptom was improved in some extent after operation. No looseness or breakage of screw occurred and bony fusion was achieved in all cases. Conclusion: C1, 2 pedicle screw fixation is a reliable method for atlanto-axial instability. Accurate rate of insertion can be improved by surgical CT navigation. Disclosure of Interest None declared